Analisis Pendapatan Usahatani Jagung Hibrida (Zeamays L) di Kelompok Tani Jirojaro Di Desa Blatatatin Kecamatan Kangae Kabupaten Sikka - Ayustus Frandi Valmon; Sarlina Noni; Gabriel Otan Apelabi (Fakultas Pertanian, Universitas Nusa Nipa, 2024)
Hybrid corn (Zea mays L.) is one of the important food commodities that has a strategic role in supporting food security and increasing farmers’ income. In Sikka Regency, East Nusa Tenggara Province, corn is widely cultivated by farmers. However, the productivity of corn farming still faces various constraints, such as limited use of production inputs, suboptimal cultivation technology, and low efficiency in farm management. This study aims to determine the level of income and the economic feasibility of hybrid corn farming in the Jirojaro Farmer Group in Blatatatin Village, Kangae District, Sikka Regency. This research was conducted in July 2024 using a purposive method to determine the research location. The respondents consisted of 30 farmers who were all members of the Jirojaro Farmer Group, selected using a saturated sampling method. The data used consisted of primary data obtained through interviews using questionnaires and field observations, as well as secondary data obtained from various literature sources and related institutions. Data analysis included cost analysis, revenue analysis, farm income analysis, business feasibility analysis using the R/C ratio, and Break Even Point (BEP) analysis. The results showed that the average total production cost was IDR 2,228,466.3 per planting season, with an average revenue of IDR 6,504,000. The average income earned by farmers was IDR 4,275,533.7 per planting season. The R/C ratio value of 2.91 (>1) indicates that hybrid corn farming is feasible and profitable to operate.